2009
DOI: 10.1186/1471-213x-9-25
|View full text |Cite
|
Sign up to set email alerts
|

Role of the 2 zebrafish survivingenes in vasculo-angiogenesis, neurogenesis, cardiogenesis and hematopoiesis

Abstract: Background Normal growth and development of organisms requires maintenance of a dynamic balance between systems that promote cell survival and those that induce apoptosis. The molecular mechanisms that regulate these processes remain poorly understood, and thus further in vivo study is required. Survivin is a member of the inhibitor of apoptosis protein (IAP) family, that uniquely also promotes mitosis and cell proliferation. Postnatally, survivin is hardly detected in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 52 publications
4
29
0
1
Order By: Relevance
“…Several studies have reported the essential role of survivin in premature brain development, and that defects in its expression exhibited abnormal brain hypoplasty and immature fetal deaths. 4,57 It was also reported to have neuroprotective effects where it colocalized with active Cas-3 and protected astrocytes after brain injury. 58 Given the role of endogenous survivin in cell-cycle progression, it plays a prominent role in the spindle-fiber formation interacting with the microtubules and organizes the CPC, complexing with aurora B kinases and INCENP.…”
Section: Proliferative Effects Of Surr9-c84amentioning
confidence: 99%
“…Several studies have reported the essential role of survivin in premature brain development, and that defects in its expression exhibited abnormal brain hypoplasty and immature fetal deaths. 4,57 It was also reported to have neuroprotective effects where it colocalized with active Cas-3 and protected astrocytes after brain injury. 58 Given the role of endogenous survivin in cell-cycle progression, it plays a prominent role in the spindle-fiber formation interacting with the microtubules and organizes the CPC, complexing with aurora B kinases and INCENP.…”
Section: Proliferative Effects Of Surr9-c84amentioning
confidence: 99%
“…6 In this direction, it is noteworthy to mention that netrin-1 disruption phenotype closely resembles that observed after silencing of three proteins involved in anti-apoptotic signaling in zebrafish, two IAP, BIRC5 and survivin, and the VEGF receptor Neuropilin-1: in each case, excess of apoptosis induced by silencing of each of these genes results in absence and/or abnormalities of ISVs that are similar to those observed in netrin-1a absence. 25,34,35 This was an argument in favor of netrin-1 pro-survival effect upon developmental angiogenesis. We have indeed observed that netrin-1 silencing leads to increase cell death in zebrafish embryos and that ISVs abnormalities could be restored by treatment of the embryos with antiapoptotic drug targeting caspases activity.…”
Section: Netrin-1 Role In Angiogenesis: Further Enlightenments Towardmentioning
confidence: 99%
“…Indeed, the knockdown of birc5a leads to multiple defects including in the nervous system, the cardiovascular system and the hematopoietic system. Interestingly, this phenotype was rescued by ectopic expression of both birc5 paralogs, suggesting the existence of functional redundancy during embryogenesis [20,21].…”
Section: Caspase Inhibitorsmentioning
confidence: 89%